1974
DOI: 10.3171/jns.1974.41.1.0020
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular perfusion in cats with kaolin-induced hydrocephalus

Abstract: ✓ Cats were made hydrocephalic by cisternal instillation of kaolin. Three to 8 weeks later it was found by perfusion between the ventricular system and the spinal subarachnoid space that communication had been reestablished through a demonstrably dilated central canal of the spinal cord. Absorption of fluid from the ventricular system, measured both by ventriculospinal perfusion and, after ligation of the spinal cord, by perfusion between the lateral ventricles, was found to be indistinguishable from zero over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(29 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Hakim et al (1976) also suggested that new channels connecting the ventricles to the subarachnoid space may develop. For example, a dilated central canal of the spinal cord, connecting the ventricles to the spinal subarachnoid space, was described in experimental hydrocephalus induced by injecting kaolin into the subarachnoid space at the base of the brain in dogs (McLaurin et al, 1954) and cats (Becker et al, 1972;Eisenberg et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hakim et al (1976) also suggested that new channels connecting the ventricles to the subarachnoid space may develop. For example, a dilated central canal of the spinal cord, connecting the ventricles to the spinal subarachnoid space, was described in experimental hydrocephalus induced by injecting kaolin into the subarachnoid space at the base of the brain in dogs (McLaurin et al, 1954) and cats (Becker et al, 1972;Eisenberg et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Eisenberg et al (1974) found that dye injected into the ventricles of cats with kaolin induced hydrocepha-lus (KIH) appears in the spinal subarachnoid space within a few minutes. The capacity to absorb CSF decreases to zero when the spinal cord is ligated.…”
Section: Introductionmentioning
confidence: 99%
“…[22] demonstrated, by perfusion between the ventri cular system and the spinal subarachnoid space, that communication had been re-established through the demonstrably dilated CC in kaolin-in duced hydrocephalic cats.…”
Section: Discussionmentioning
confidence: 99%
“…The dye was contained within the ventricles and the central canal. No leak was detected over the brain, in the area of the olfactory nerves, or around the spinal cord [3], Ventricular obstruction, therefore, seemed to have been complete.…”
Section: Generalmentioning
confidence: 99%
“…Previous studies [1,3,4,11,13] clarified certain physiological parameters pertaining to cerebrospinal fluid (CSF) dynamics in hydrocephalus. Those studies were performed on adult animals and the ventricular volumes described were considerably smaller in comparison to those seen in sick infants [4,[14][15][16] unless special techniques were employed [2,6,7], These studies also suggested the possibility of the 'arrest' of the hydrocephalic process in a proportion greater than that seen in humans [9].…”
Section: Introductionmentioning
confidence: 99%